Of Cows and Women: Gendered Human-Animal Relationships in Finnish Agriculture - Taija Kaarlenkaski (Relations, 2014)
In the Nordic countries, the tending of cattle was regarded as women’s work in agrarian culture. This was also the case in Finland, where the gendered division of labor on farms was fairly strict until the mid-20th century. The purpose of this article is to discuss the gendered representations of animal husbandry and cows in written narratives collected in a public writing competition. The writing competition about the cow was arranged in 2004 by the Finnish Literature Society and the Union of Rural Education and Culture, and an exceptionally high number of stories were sent to the competition. It will be argued in the article that gender, embodiment and emotions are often intertwined in the practices of animal husbandry. According to my interpretation, one reason for the division of labor was the bodily relationship with cows, which was allowed for women but not for men. In addition to the division of work, there are other aspects of cattle tending in which gender and embodiment emerge in the narratives. For example, the cows are also frequently gendered: one typical way for especially women to represent cows is to emphasize their gender and to articulate solidarity between females.